Congenital Membrane Causing Duodenal Obstruction and Malpositioning of the Descending Colon - Chee-Chee Koh; Sheng-Hong Tseng; Chia-Chi Weng; Yun Chen (Elsevier, 2013)
A congenital membrane without intestinal malrotation is a rare cause of duodenal obstruction. Here we present an 11-year-old girl who had suffered from intermittent abdominal cramping pain and vomiting for more than 5 years. The image studies, including a plain abdomen roentgenogram and sonogram, showed no definite diagnosis. The upper gastrointestinal series and small bowel series showed the contrast was static over the third portion of the duodenum and the descending colon pulled up toward the epigastric area. Laparoscopic exploration revealed a congenital membrane extending from the right-side paraduodenal peritoneum through the third portion of the duodenum to the descending colon, which had caused obstruction of the third portion of the duodenum and malpositioning of the descending colon. To the best of our knowledge, this is the first case report in the literature where a congenital membrane caused both duodenal obstruction and malpositioning of the descending colon.